Four new species of Moneuptychia (Lepidoptera: Satyrinae: Euptychiina) from Brazil - Freitas, André V. L.; Barbosa, Eduardo P.; Siewert, Ricardo R.; Mielke, Olaf. H. H.; Zacca, Thamara; Azeredo-Espin, Ana Maria L. (Zootaxa, 2015)
This paper describes four new species of Moneuptychia as follows: M. montana Freitas, M. vitellina Freitas & Barbosa, M. pervagata Freitas, Siewert & Mielke and M. wahlbergi Freitas, Barbosa, Siewert & Mielke from south and southeastern Brazil. Details are presented on the morphology of adults of all species, and immature stages for two species, and we discuss the taxonomy and identification of the genus Moneuptychia. The mitochondrial CoxI “barcode” region was used for exploring the utility of this DNA marker to identify these species, giving strong support for all new species.